Association between exercise program participation and hospitalization of older adults - Wright, D.S.; Zhou, B.; Wright, C.X.; Axtell, R.S.; Mangi, A.; Safdar, B. (American Journal of Preventive Medicine, 2024)
Introduction: Government and insurance sponsored exercise programs have demonstrated decreased hospitalizations, but it is unclear if this is the case for self-referred programs. Methods: In this retrospective cohort study from 2013 to 2020, older adults who participated for at least three months at a community-based exercise center (participants) were compared with those who did not (nonparticipants). Each completed a baseline physical assessment and periodic reassessments thereafter. These data were paired with regional hospital data and a national mortality database. Statistical analysis and modeling were performed from 2020 to 2023. Survival to all-cause hospitalization was assessed with a priori subgroup comparison by gender and cox proportional hazard modeling by age, gender, and comorbidities. Results: The cohort included 718 adults, mean age 69.5 years (SD 8.4), with 411 (57.2%) participants and 307 nonparticipants. Mean follow-up was 26.7 months. Participants had similar baseline measures of fitness (p>0.05) but were more likely to be retired and less likely to have diabetes or prior stroke than nonparticipants. Sustained participation was associated with a reduced rate of all-cause hospitalization (9.0% vs. 12.7%, p=0.02), even when adjusted (HR 0.54; 95% CI 0.34, 0.87, p=0.01). This decrease was noted only in women (p=0.03) but not in men (p=0.49), gender was nonsignificant after adjustment for comorbidities (p=0.15). Conclusions: Exercise program participation was independently associated with decreased risk of all-cause hospitalization, with possible differential effects by gender. Further randomized trials of the benefits of personalized exercise programs are warranted to assess sex- and gender-specific effects. © 2024 Elsevier Inc.
Keywords: dept.hms; peer-reviewed